2016
DOI: 10.1002/etc.3547
|View full text |Cite
|
Sign up to set email alerts
|

Intersex and liver alterations induced by long‐term sublethal exposure to 17α‐ethinylestradiol in adult male Cnesterodon decemmaculatus (Pisces: Poeciliidae)

Abstract: The aim of the present study was to assess the responses of the gonopodium morphology and the gonadal and liver histology of adult male Cnesterodon decemmaculatus to sublethal long-term exposure concentrations of 17α-ethinylestradiol (EE2). Two experiments were conducted exposing the fish to waterborne concentrations of EE2 ranging from 20 ng/L to 200 ng/L for 8 wk, 12 wk, and 16 wk. Intersex gonads were observed after 8 wk and 16 wk in fish exposed to 200 ng EE2/L and 100 ng EE2/L, respectively. Oocytes' deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 40 publications
(49 reference statements)
0
19
0
Order By: Relevance
“…A major limitation of the developed midge BCF model is its restricted application to neutral organic compounds. A logical next step is to explore how well the same reduced toxicokinetic framework may be extended toward ionizable organic compounds, which have been gaining attention in recent years for their ubiquity and potent ecotoxicological effects on aquatic organisms (Parolini et al 2017; Thorngren et al 2017; Young et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A major limitation of the developed midge BCF model is its restricted application to neutral organic compounds. A logical next step is to explore how well the same reduced toxicokinetic framework may be extended toward ionizable organic compounds, which have been gaining attention in recent years for their ubiquity and potent ecotoxicological effects on aquatic organisms (Parolini et al 2017; Thorngren et al 2017; Young et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…With growing scientific and public concern, PIOCs have emerged as contaminants of major concern (Boxall et al ). They include many pharmaceuticals, pesticides, and industrial chemicals with potent ecotoxicological effects (de Brito Rodrigues et al ; Parolini et al ; Thorngren et al ; Villeneuve et al ; Young et al ). Aquatic organisms are particularly vulnerable to their presence because a number of PIOCs are detected in different water bodies and can persist through harsh treatment processes (Maruya et al ; Cantwell et al ; Sadaria et al ).…”
Section: Discussionmentioning
confidence: 99%
“…The lower value of GSI is thought to occur due to the disturbance development of male fish gonads during spermatogenesis. Several studies also reported a decrease in the value of GSI in male fish due to exposure to various types of pollutants, for instance, mercury, cadmium, and 17αethinylestradiol [20,21,22].…”
Section: Resultsmentioning
confidence: 96%